(untitled) (Research, Society and Development, 2022)
Distance learning gained more space during the Covid-19 pandemic, because with a delicate scenario, with something new and unknown that the pandemic brought, remote learning was the way out to continue classes. Schools, educational institutions, remained behind closed doors to maintain social distance, at home teachers and students had to adapt, and reinvent themselves to ensure knowledge, several video recording mechanisms were used, classes, activities sent by through the social networks, as well as the use of remote platforms for digital teaching, which played a leading role in this process. In this way, this study aims to analyze the perceptions of the academics of the Physiotherapy course at the University of the State of Pará in the municipality of Santarém about the quality of remote and face-to-face teaching amid the Covid-19 Pandemic. Data collection took place through collective interviews, using focus groups, where the interviews followed a semi-structured script. In this way, two groups were carried out, with six academics each, with a total of 12 participants. It is concluded that the non-presential teaching modality gained space through many challenges and paradigms for society as a whole, but mainly for teachers and students. Although some challenges have been overcome, there are many others that must be experienced, rethought and overcome through investment practices in education.